ANALISIS PERBANDINGAN KEBANGKRUTAN MODEL ALTMAN, MODEL SPRINGATE, DAN MODEL ZMIJEWSKI PADA PERUSAHAAN YANG TERGABUNG DALAM GRUP BAKRIE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2012 - NUR RHOMADHONA, MUHAMMAD Nur (Jurnal Akuntansi AKUNESA, 2014)
The research aims to determine how the bankruptcy prediction companies that are in the Bakrie Group listed on the Indonesian Stock Exchange 2010-2012. This research used three bankruptcy prediction model; the Altman model, the model Springate and Zmijewski model. This research will want to know whether the future of existing companies in the Bakrie Group will be bankrupt or not, because it is known that companies that are in the Bakrie Group has a large debt that requires a subsidiary company to sell assets to pay off debts and to get sufficient funds in its operations. The result of this research is that if you add up all the models and compared overall between companies that belong to the category of bankruptcy and companies that fall into the healthy category, the average firm in Bakrie Group could still be said to the category of a healthy company.Keywords : Bakrie Group, bankruptcy index, Altman model, model Springate and Zmijewski model